Regulation of erythroid differentiation in K562 cells by the EPAS1-IRS2 axis under hypoxic conditions - Gao, Zhan; Li, Zhicai; Li, Xiaowei; Xiao, Jun; Li, Cuiying (Frontiers in Cell and Developmental Biology, 2023)
Red blood cells (RBCs) produced in vitro have the potential to alleviate the worldwide demand for blood transfusion. Hematopoietic cell differentiation and proliferation are triggered by numerous cellular physiological processes, including low oxygen concentration (<5%). In addition, hypoxia inducible factor 2α (HIF-2α) and insulin receptor substrate 2 (IRS2) were found to be involved in the progression of erythroid differentiation. However, the function of the HIF-2α-IRS2 axis in the progression of erythropoiesis is not yet fully understood. Therefore, we used an ex vivo model of erythropoiesis generated from K562 cells transduced with shEPSAS1 at 5% O2 in the presence or absence of the IRS2 inhibitor NT157. We observed that erythroid differentiation was accelerated in K562 cells by hypoxia. Conversely, knockdown of EPAS1 expression reduced IRS2 expression and erythroid differentiation. Intriguingly, inhibition of IRS2 could impair the progression of hypoxia-induced erythropoiesis without affecting EPAS1 expression. These findings indicated that the EPAS1-IRS2 axis may be a crucial pathway that regulates erythropoiesis and that drugs targeting this pathway may become promising agents for promoting erythroid differentiation.